Delivering stem cells to the healthy heart on biological sutures: effects on regional mechanical function. (21st April 2014) - Tao, Ze‐Wei; Favreau, John T.; Guyette, Jacques P.; Hansen, Katrina J.; Lessard, Jeffrey; Burford, Evans; Pins, George D.; Gaudette, Glenn R.
Abstract: Current cardiac cell therapies cannot effectively target and retain cells in a specific area of the heart. Cell‐seeded biological sutures were previously developed to overcome this limitation, demonstrating targeted delivery with > 60% cell retention. In this study, both cell‐seeded and non‐seeded fibrin‐based biological sutures were implanted into normal functioning rat hearts to determine the effects on mechanical function and fibrotic response. Human mesenchymal stem cells (hMSCs) were used based on previous work and established cardioprotective effects. Non‐seeded or hMSC‐seeded sutures were implanted into healthy athymic rat hearts. Before cell seeding, hMSCs were passively loaded with quantum dot nanoparticles. One week after implantation, regional stroke work index and systolic area of contraction (SAC) were evaluated on the epicardial surface above the suture. Cell delivery and retention were confirmed by quantum dot tracking, and the fibrotic tissue area was evaluated. Non‐seeded biological sutures decreased SAC near the suture from 0.20 ± 0.01 measured in sham hearts to 0.08 ± 0.02, whereas hMSC‐seeded biological sutures dampened the decrease in SAC (0.15 ± 0.02). Non‐seeded sutures also displayed a small amount of fibrosis around the sutures (1.0 ± 0.1 mm 2 ). Sutures seeded with hMSCs displayed a significant reduction in fibrosis (0.5 ± 0.1 mm 2, p < 0.001), with quantum dot‐labelled hMSCs found along the suture track. These results show that the addition of hMSCs attenuates the fibrotic response observed with non‐seeded sutures, leading to improved regional mechanics of the implantation region. Copyright © 2014 John Wiley & Sons, Ltd.